WONOSOBO GELORA STADIUM DESIGN WITH A FUTURISTIC ARCHITECTURAL APPROACH - Setiawan, Agus; Hermawan, Hermawan; Hendriani, Adinda Septi (Nacreva Publisher, 2024)
Stadiums are the most influential supporting facilities for the sport of football in the world. Having a stadium can add pride to an area. Gelora Wonosobo Stadium is a football stadium in Wonosobo district as well as a stadium that will be used as the headquarters for the PSIW football club (Wonosobo Indonesian Football Association). The club, which has the nickname Laskar Kolodete, was previously headquartered at the Kalianget Stadium which is adjacent to the Kalianget Recreation Park and has not yet received proper stadium facilities and also cannot be called a stadium considering how it is now, therefore the Gelora Wonosobo Stadium was built which is located on Jalan Wonosobo. Kertek is opposite the Dewasni Café Restaurant, the choice of location also takes into consideration several things, namely land use, accessibility, supporting facilities for the surrounding environment and city utilities so that it will make it easier for stadium users. Gelora Wonosobo Stadium is a district class B type stadium which has FIFA standard facilities and has a capacity of approximately 20,000 spectators with a distribution of 400 VIP/VVIP spectator seats, 18,600 general spectator seats, 1000 disabled spectator seats which is 5% of the general spectators. The Gelora Wonosobo Stadium will adopt a modern, futuristic architectural style and without an athletics track. With the absence of an athletics track, the distance between the field and the stands will be closer, so there will be a distance between the stands and the field or a safety zone to see the less orderly behavior of the Indonesian people.